The Impact of Digitalization on the Financial Security of Financial Market Participants in Ukraine in the Context of its Benefits and Risk Minimization - N. B. DOBRIANSKA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article highlights the impact of digitalization on the financial security of financial market participants (FMPs) in Ukraine, taking into account its advantages and ways to reduce risks. The approaches of domestic and foreign scientists to studying the issue of financial security of FMPs, e.g. households, were analyzed, with assessing the advantages, disadvantages and risks associated with the implementation of digitalization in the financial sector. The principal digitalization components for FMPs are characterized. The main advantages of digitalization for FMPs and the threats (risks) that may arise from the use of digital technologies in financial transactions were investigated and summarized. The essence of individual and system threats and risks for FMPs using digital technologies was highlighted. The financial security-related problems faced by FMPs in Ukraine in the digitalized environment were outlined. Special attention was paid to the problems of digital financial literacy, cybersecurity, and regulation pertaining to digitalization tools in the financial sector. The conclusion was drawn about the existing disparities in digital transformation, caused by difficulties of technological, personnel, and financial origin. It is emphasized that, despite the variety of digital tools, there are still areas that have not yet been covered by digitalization. The main and critically important advantages of the digitalization process and ways of their effective use in in the financial activities are highlighted. The mechanisms for avoiding the negative consequences of digitalization processes and minimizing the FMPs’ risks associated with them were summarized. The main directions for overcoming internal obstacles and ensuring the FMPs’ susceptibility to high-tech initiatives and digital transformation were outlined. As a result of the research, recommendations for increasing the financial security of FMPs in the digitalized environment were made.